2010
DOI: 10.1243/13506501jet772
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation formation and modelling for fluid film bearings: A review

Abstract: Even though the list of references associated with this review is rather extensive, in no way does it exhaust the vast literature dedicated to the study of cavitation. The intent was to summarize (i) advances in analytical and numerical modelling, (ii) draw attention to the thermodynamic aspects of cavitation, and (iii) do so while reflecting on physical or experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 55 publications
4
112
0
4
Order By: Relevance
“…According to the Payvar-Salant [27,28] model, the steady-state mass-conservation Reynolds equation, taking cavitation into account, in a Cartesian coordinate system can be written as Equation (2) [29]:…”
Section: Methodsmentioning
confidence: 99%
“…According to the Payvar-Salant [27,28] model, the steady-state mass-conservation Reynolds equation, taking cavitation into account, in a Cartesian coordinate system can be written as Equation (2) [29]:…”
Section: Methodsmentioning
confidence: 99%
“…Shyu et al [16] analyzed the velocity and temperature distributions, and pressure distribution using the Legendre collocation method, the bulk-flow model and Elord' s cavitation algorithm. Braun et al [17] learned that the cavitation pressure is not common and changed with the axial and circumferential location by experiment. Croper et al [18] observed that cavitation pressure is not common and the cavitation shape can be acquired by shear mechanism.…”
Section: B Study Of Cavitation On Bearing Performancementioning
confidence: 99%
“…Many authors have offered analytical and numerical solutions, the list of excellent contributions being too long to do it justice here. The interested reader is further referred to review publications of Dowson et al [6], Brewe et al [7], and Braun and Hannon [8]. Zuber and Dougherty [9] in 1982 were the first to propose a model for a homogeneous two-phase lubricating film mixture in conjunction with the RE.…”
Section: Introductionmentioning
confidence: 99%